Curcumin in Autoimmune and Rheumatic Diseases - Yang, Melissa (Nutrients, 2019)
Over recent decades, many clinical trials on curcumin supplementation have been conducted on various autoimmune diseases including osteoarthritis, type 2 diabetes, and ulcerative colitis patients. This review attempts to summarize the highlights from these clinical trials. The efficacy of curcumin either alone or in conjunction with existing treatment was evaluated. Sixteen clinical trials have been conducted in osteoarthritis, 14 of which yielded significant improvements in multiple disease parameters. Eight trials have been conducted in type 2 diabetes, all yielding significant improvement in clinical or laboratory outcomes. Three trials were in ulcerative colitis, two of which yielded significant improvement in at least one clinical outcome. Additionally, two clinical trials on rheumatoid arthritis, one clinical trial on lupus nephritis, and two clinical trials on multiple sclerosis resulted in inconclusive results. Longer duration, larger cohort size, and multiple dosage arm trials are warranted to establish the long term benefits of curcumin supplementation. Multiple mechanisms of action of curcumin on these diseases have been researched, including the modulation of the eicosanoid pathway towards a more anti-inflammatory pathway, and the modulation of serum lipid levels towards a favorable profile. Overall, curcumin supplementation emerges as an effective therapeutic agent with minimal-to-no side effects, which can be added in conjunction to current standard of care.